The carriage of group B streptococci in Turkish pregnant women and its transmission rate in newborns and serotype distribution - Eren, Aynur; Küçükercan, Metin; Oğuzoğlu, Naz; Unal, Nuriye; Karateke, Ateş (The Turkish Journal of Pediatrics, 2005)
The prevalence of group B streptococci (GBS) colonization was studied in 500 pregnant women and their newborn infants by collecting vaginal and rectal swabs from mothers, and umbilical and throat swabs from their infants. Forty-six isolates of GBS were obtained from mothers’ specimens and eight from neonates. Maternal and infant colonization rates were found to be 9.2% and 1.6%, respectively. Vertical transmission rate was 15.2%. Additionally, serotypes and antimicrobial susceptibility of 54 isolates of GBS were determined. Type Ia, II and III were common serotypes among GBS isolates from mothers and infants. When evaluating the factors that affect GBS carriage, age, socio-economic status and education level of pregnant women were important for carriage, while use of intrauterine device and parity were unrelated. No resistance to ampicillin, penicillin, ceftriaxone or vancomycin was found by disk diffusion method. A high level of resistance against tetracycline was noted (91%). Although invasive serotypes are predominant, the rarity of GBS disease in Turkish infants may be due to low rates of maternal carriage or to their possessing protective levels of GBS-specific IgG antibody in their sera.